Pengukuran Metrik Kompleksitas Web Service Sekolah - Riza, Ahmad; Anshori, Mohamad Alif Irfan; Arrazy, Farrah; Yaqin, M. Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
The Complexity Metric Diagram is a method of measuring software complexity. This method uses Class Diagrams as test parameters. This study uses test data from previous research regarding the design of Information Systems accompanied by Class Diagrams with case studies of School Academic Information Systems. The facts found in the field that school software developers do not conduct application audits so it is not ripe to face problems that will arise in the future. The results of the calculation of the complexity metrics in the School Academic Information System produce an output of 993.32 units.